The Moro Muslim Conflict in the Philippines: A Postcolonialism Perspective - Choiroh, Wahyuni Nuryatul (Islah: Journal of Islamic Literature and History, 2023)
This article discusses the long and complex history of the Moro Nation, starting with the presence of Islam which flourished in the Southern Philippines. Then Spain came and the United States brought political and Christianization missions until the time of Philippine independence. The term "Moro" refers to the bad stigma of the Spanish colonials to Filipino Muslims because of their rejection and rebellion against the colonizers. Therefore, this literature review aims to examine the characteristics of Moro Muslims in three phases of struggle, i.e., the period of struggle against Spanish colonialism for 375 years, the struggle for independence from United States imperialism, and post-independence which was transferred to the Christian government of the Northern Philippines, so that the Moro Nation fought against the government of its own country as Jihad fi Sabilillah. By means of postcolonialism studies that define criticism of cultural appropriation and exploitation by colonialists, postcolonialism identity in a negotiation carries out disclosure of the deception given to it and brings others or otherness to itself. In this regard, the stigmatization has become a breakthrough spirit as a defense and struggle of the Moro Muslim community in the form of Jihad from discrimination during colonialism and post-independence.